Analysis of The Effect of Chronic Disease Management Program (Prolanis) on Patient Satisfaction Level for Hypertensive Patients at Baros Health Center and Rangkasbitung Health Center in Lebak Regency, Banten Province - Restu Restiani; Shirly Kumala; Prih Sarnianto (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
In order to overcome hypertension which has become a serious public health problem, the Government through BPJS Health is taking a proactive approach. One of them is by involving first-level health facilities (FKTP), especially Health centers, to carry out promotive and preventive efforts known as the Chronic Disease Management Program (Prolanis). Prolanis' goal is to encourage people with chronic diseases, for example, hypertension, to achieve an optimal quality of life so as to prevent complications. This study aims to find out that the implementation of Prolanis can indeed increase patient satisfaction with mild and moderate hypertension at the Health center so that it is feasible to be funded by BPJS Health by knowing the characteristics and satisfaction of hypertensive patients at two Puskesmas, namely the Baros Health Center which has implemented Prolanis and the Rangkasbitung Health Center which has not implemented Prolanis. Data were obtained through questionnaires distributed to hypertensive patients in two health centers, namely the Baros Health Center and Rangkasbitung Health Center. The independent variables used in the study are patient characteristics Meanwhile, the dependent variable is patient satisfaction. Data were analyzed by means of different test analyses using SPSS version 23.0. The results showed that the characteristics of the patients were different for the Baros Health Center and Rangkasbitung Health Center. Judging from satisfaction based on its characteristics, age has different satisfaction both at the Baros Health Center and at the Rangkasbitung Health Center. Judging from the patient's satisfaction related to knowledge and also Prolanis services in general for the Baros Health Center area it is higher (satisfied) and similarly, the blood pressure is more controlled compared to the Rangkasbitung Health Center.